Seasonal changes in food composition of the brown bear ( Ursus arctos) from the edge of its occurrence – Eastern Carpathians (Slovakia) - Štofik, Jozef; Merganič, Ján; Merganičová, Katarína; Saniga, Miroslav; null, null
The food composition of the brown bear diet was studied on the basis of 215 excrement samples, which were collected in 2008-2010 in the area of the Eastern Carpathians (Poloniny National Park). The seasonal changes in food composition reflected the supply of the environment, which is nowadays influenced by human activities. This situation resulted in a stronger adaptation of bear to anthropogenic food sources of plant origin compared to historical data from the Carpathians. We identified diagnostic groups and food components consumed by bears in individual seasons of the evaluated period. In spring, crops provided by hunters were found to be the diagnostic group; and corn, silage, rape, bark and wood were diagnostic components. In summer, invertebrates were the diagnostic group; and ants, cherries and grass were the diagnostic components. In autumn, fruit were the diagnostic group; and apples, pears, blackberries, plums and acorns were the diagnostic components. In winter, hard mast and crops provided by hunters were diagnostic groups; and beechnuts, sunflower, rape, wheat, corn and corn silage were diagnostic components. From the nutritional point of view, crops provided by hunters dominated in spring and summer, and hard mast dominated in autumn and winter.